1982
DOI: 10.2466/pr0.1982.50.2.639
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural MMPI Comparison of Alcoholics

Abstract: MMPI Profiles of 11 Caucasian, 11 Hispanic American, and 11 American Indian alcoholics were compared. The subjects were chosen randomly from among veterans in treatment for alcoholism at a small VA Medical Center. Subjects represented similar secondary diagnoses and did not differ significantly in age or education. One-way nonrepeated-measures analyses of variance on validity, clinical and the MacAndrews Alcoholism Scales showed significance only for Scale 2 scores, elevated for the Hispanic American group but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Various investigators (English and Curtin, 1975and Pattison et al, 1979, 1969 have provided evidence that alcohol treatment programs even within the same geographic area can have different admission criteria and thus attract different types of patients. Page and Bozlee (1982) found very similar MMPI profiles, conforming to previously published alcoholic MMPI prototypes, when Caucasian, Hispanic-American, and American Indian alcoholics were compared. All were veterans in treatment at the same V.A.…”
Section: Factors Contributing To Diversitysupporting
confidence: 87%
“…Various investigators (English and Curtin, 1975and Pattison et al, 1979, 1969 have provided evidence that alcohol treatment programs even within the same geographic area can have different admission criteria and thus attract different types of patients. Page and Bozlee (1982) found very similar MMPI profiles, conforming to previously published alcoholic MMPI prototypes, when Caucasian, Hispanic-American, and American Indian alcoholics were compared. All were veterans in treatment at the same V.A.…”
Section: Factors Contributing To Diversitysupporting
confidence: 87%
“…Differences in the mean profiles of cultural groups were reported by Page and Bozlee (1982), who found the 49 two-point code characteristic of White alcoholics, the 24 two-point code characteristic of Hispanic alcoholics, and the 96 two-point code characteristic of American Indian alcoholics. In contrast, Uecker, Boutilier, and Richardson (1980) reported that the characteristic mean profile for their American Indian alcoholics was a 24 two-point code.…”
Section: Research Based On Profile Configurationsmentioning
confidence: 92%
“…Elevation on Scale 4 has been reported for alcoholic inpatients (English & Curtin, 1975; Goldstein & Linden, 1969; Hill, Haertzen, & Davis, 1962; MacAndrew, 1978; Mayo, 1985; McWilliams & Brown, 1977; Rohan, Tatro, & Rotman, 1969) and outpatients (Hampton, 1953; Hewitt, 1943; MacAndrew, 1978; MacAndrew & Geertsma, 1963; Rosen, 1960). Both Black alcoholics and White alcoholics have produced elevated Scale 4 scores (Mayo, 1985; Walters, Greene, & Jeffrey, 1984; Walters, Greene, Jeffrey, Kruzich, & Haskin, 1983), and data have indicated that Hispanic alcoholics (Page & Bozlee, 1982) and American Indian alcoholics (Page & Bozlee, 1982; Pollack & Shore, 1980) tend to produce relatively high scores on Scale 4 as well. Correspondingly, Scale 4 elevations have been found for both male and female alcoholics (Curlee, 1970; Eshbaugh, Tosi, & Hoyt, 1980; Hewitt, 1943; Jansen & Hoffmann, 1973; MacAndrew, 1978; Manson, 1949; McKenna & Pickens, 1983; Rosen, 1960; Zelen, Fox, Gould, & Olson, 1966).…”
Section: Research Based On Standard Mmpi Scales: Scale 4 Elevationsmentioning
confidence: 99%
“…The differences that are found generally have been attributed to personality disruption, serious emotional disturbance, and poor adjustment (Bryde, 1966; Kline et al, 1973; Krush, Bjork, Sindell, & Nelle, 1966; Townsley & Goldstein, 1977) and, more recently, to cultural differences (Pollack & Shore, 1980). Other studies detected few, if any, discernable differences between the MMPIs of American Indians and non-Indian groups (Page & Bozlee, 1982) or attributed differences that were observed as being largely due to sociodemographic factors (Bernstein, Teng, Granneman, & Garbin, 1987; Hoffman et al, 1985; Venn, 1988; Westermeyer, 1972). The conclusions that can be based on these studies are restricted by limitations in their research designs, including small sample sizes, absence of criteria for defining American Indians, lack of comparison groups, inclusion of only men, and reliance on captive populations, such as prisoners, boarding school students, and alcoholic or psychiatric patients in treatment settings.…”
mentioning
confidence: 95%